Respostas

A melhor resposta!
2014-06-23T16:57:07-03:00
B)
2x + 3y = -2
-2x + y = -6
   0 +4y = -8 => y = -8/4 => y = -2
 -2x -2 = -6 =>  -2x = -6 + 2 => -2x = -4 => x = 2
..............
c)
x + 3y = 1
2x - 3y = 8
3x = 9 => x = 9/3 => x = 3

3 + 3y = 1 => 3y = 1 - 3 => 3y = -2 => y = -2/3
................
d)
x + 2y = 7                       x + 2y = 7
4x - y = 10 (-2) ==>> -8x + 2y = -20
                                      -7x = -13 => x = 13/7
4.13/7 - y = 10 => -y = 10 - 52/7 => -y = (70-52)/7 => -y = 18/7 => y = -18/7
1 5 1